2020
DOI: 10.5433/1679-0359.2020v41n6supl2p3351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rehydration with whey and inoculation with Lactobacillus plantarum and Propionibacterium acidipropionici on the chemical composition, microbiological dynamics, and fermentative losses of corn grain silage

Abstract: The objective of this study was to compare rehydrated corn grain silages using water or whey and inoculated (Lactobacillus plantarum and Propionibacterium acidipropionici) or not. We also verified whether rehydration with whey associated with the bacterial inoculant improves material conservation. The treatments were as follows: silages rehydrated with water without inoculant (SWa); silages rehydrated with water and inoculated (SWaI); silages rehydrated with whey without inoculant (SWe); silages rehydrated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Pádua et al [93], evaluating the effects of urea doses on potato grass hay (Paspalum Notatum), observed that the CP content increased with increasing levels of urea used in the study. Similarly, Sousa et al [44], evaluating the chemical composition of corn straw ammoniated with urea added at 0, 2, 4, 6, and 8% of total DM, observed an increase in CP content with the inclusion of doses of urea with values ranging from 5.36 to 11.2 (%DM).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Pádua et al [93], evaluating the effects of urea doses on potato grass hay (Paspalum Notatum), observed that the CP content increased with increasing levels of urea used in the study. Similarly, Sousa et al [44], evaluating the chemical composition of corn straw ammoniated with urea added at 0, 2, 4, 6, and 8% of total DM, observed an increase in CP content with the inclusion of doses of urea with values ranging from 5.36 to 11.2 (%DM).…”
Section: Discussionmentioning
confidence: 73%
“…Although it is not possible to compare NDF content before and after ensiling in this review because there are no data on the chemical composition of the mass before ensiling, previous studies, such as that of Rezende et al [42], indicate greater reductions in NDF in silage when whey is used to rehydrate corn grains when compared to water. However, Sousa et al [44] and Cruz et al [45] found different effects of whey compared to water, making it difficult to evaluate this additive's intrinsic effect in reducing the silage's NDF content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation